2016
DOI: 10.1016/j.jogn.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Women's Preventive Services Guidelines in the Affordable Care Act

Abstract: Objective To assess the adherence of women’s health providers in New Mexico to the Women’s Preventive Services Guidelines, now covered as part of the Affordable Care Act, and to examine how providers’ knowledge, attitudes, and external barriers are associated with adherence to these clinical guidelines. Design Cross-sectional, descriptive survey. Setting New Mexico. Participants Women’s health providers in New Mexico, including nurse practitioners, certified nurse-midwives, and family practice and obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…They also concluded that physicians with a neutral opinion used 3 times more and physicians with a positive attitude used 5 times more guidelines compared to the physicians who have negative attitudes towards the guidelines. Tinkle et al (2016) found that those who stated that they did not have the necessary facilities and time to implement the CPGs had lower rates of compliance with the CPGs than those who did not state. This finding is consistent with our research's indicating there is an inverse relationship between organizational barriers and the use of CPGs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They also concluded that physicians with a neutral opinion used 3 times more and physicians with a positive attitude used 5 times more guidelines compared to the physicians who have negative attitudes towards the guidelines. Tinkle et al (2016) found that those who stated that they did not have the necessary facilities and time to implement the CPGs had lower rates of compliance with the CPGs than those who did not state. This finding is consistent with our research's indicating there is an inverse relationship between organizational barriers and the use of CPGs.…”
Section: Discussionmentioning
confidence: 95%
“…In the study conducted by Kotzeva et al (2010), it was stated that more familiarity with CPGs and using more CPGs were associated with higher positive attitudes. In the study conducted by Tinkle et al (2016), it was determined that those who had a more positive attitude towards CPGs were more in harmony than those who had a negative and neutral attitude. The authors concluded that those who have awareness and familiarity with the guidelines adapted 2-5 times more than those who were "not aware" or "aware but not familiar".…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kotzeva et al (2010), more familiarity with the CPGs was associated with having a higher rate of positive attitude and more use of CPGs. In the study performed by Tinkle et al (2016), it was observed that those who had more positive attitude towards the CPGs had more compliance with the CPGs than those with negative and neutral attitudes. In the study carried out by Graham et al (2000), as a result of screening, the relationship between the physicians’ use of guidelines and their attitudes about guidelines, it was observed that the physicians who had a positive attitude about the guidelines were also significantly more likely to use the guidelines.…”
Section: Discussionmentioning
confidence: 97%
“…Although adherence to guidelines improves outcomes, nonadherence to guidelines was shown to be frequent 53,54 and was more likely to affect patients who were older or had cancer or other comorbidites. 52 Low adherence to guidelines reinforces that passive diffusion of evidence is unreliable.…”
Section: Improving Guideline Uptakementioning
confidence: 99%